Victim Centered, Aggressor Focused, and Bystander Friendly: A Qualitative Analysis of Bystander Intervention Strategies and Outcomes for Sexual Harassment or Assault - Ford, Kayla (Journal of interpersonal violence, 2024)
Limited qualitative research has been conducted to understand the experiences of victims of sexual harassment or assault (SHA) when a bystander intervenes. Even less research has focused on the consequences of bystander actions from the victim’s perspective, particularly regarding the aggressor’s subsequent behavior toward the victim and occurrence of verbal or physical harm to those involved. This qualitative study aimed to address these limitations with the following research questions: (a) what strategies did victims of SHA identify bystanders use when intervening? (b) what strategies were present when the aggressor’s behavior was stopped, paused, or continued toward the victim? and (c) what strategies were present when verbal or physical harm occurred to someone involved? Adult women between the ages of 18 to 30 (N = 25, college student = 80%) were interviewed about one situation of bystander intervention during SHA since the age of 16 years. Findings suggest that victims identified direct, distance, distract, delegate, and proximity strategies by bystanders. Most participants reported that the aggressor’s behavior stopped or paused following bystander action, and in these cases, at least one distance or direct strategy was reportedly used most frequently. Approximately, 24% and 8% of participants reported verbal or physical harm, respectively, to at least one party. Direct and distance strategies were most frequently mentioned in experiences of SHA that involved harm. When the aggressor’s behavior continued (i.e., was not altered during the event) despite bystander actions, strategies most frequently reported included distract, delegate, and proximity. Together, results suggest that bystander intervention training programs and future research may be needed to understand under what contexts certain strategies successfully prevent or thwart SHA while maintaining emotional and physical safety for those involved.